Determinants of loneliness and quality of life among rural community-dwelling older adults in Egypt: A cross-sectional descriptive study - Hassanat Ramadan Abdel Aziz; Ayman Mohamed El-Ashry; Ateya Megahed Ibrahim; Safia Gomaa Mohammed (Belitung Nursing Journal, 2026)
Background: Loneliness in later life is common and is strongly associated with poorer quality of life (QoL). However, evidence from rural Egypt remains limited, particularly community-based studies that concurrently examine loneliness and QoL and their health, social, religious, and leisure-related determinants. This gap limits the development of culturally appropriate nursing and community interventions for rural older adults. Objective: To assess the levels of loneliness and QoL and to identify their determinants among community-dwelling older adults in a rural Egyptian setting. Methods: A cross-sectional descriptive study was conducted between July and September 2023 in a randomly selected rural village in Sharkia Governorate, Egypt. Using multistage probability sampling, 143 community-dwelling adults aged 60 years and older were recruited. Data were collected using structured and validated questionnaires. Descriptive statistics, Pearson correlation coefficients, and multiple linear regression analyses were performed. Results: Participants had a mean age of 70.87 ± 8.50 years, and 52.4 percent were women. High loneliness was reported by 43.4 percent of participants, while 73.4 percent had low overall quality of life. Loneliness was strongly and inversely correlated with quality of life and was positively correlated with age and disease burden, while quality of life was negatively associated with age and number of chronic diseases and positively associated with education, income, social support, religious rituals, and leisure activities in bivariate analyses (all p <0.001). In exploratory multivariable analyses, quality of life was independently associated with age, education, current employment, number of chronic diseases, social support, and loneliness (R² = 0.743), while loneliness was associated with age, number of visitors, religious rituals, and leisure activities (R² = 0.451). Conclusion: Loneliness and low quality of life are highly prevalent among community dwelling older adults in rural Egypt and are closely linked to aging, chronic disease burden, social resources, and engagement in meaningful activities. For nursing practice, these findings support the routine screening of loneliness and quality of life in primary and chronic care settings, the integration of social support and activity-based interventions into care plans, and collaboration with community and faith-based organizations to deliver culturally appropriate strategies aimed at reducing loneliness and enhancing quality of life among rural older populations.